Temperature Dependence of Primary Species G(values) Formed from Radiolysis of Water by Interaction of Tritium β-Particles - Sofia Loren Butarbutar; Sriyono Sriyono; Geni Rina Sunaryo (Pusat Kajian Sistem Energi Nuklir, Badan Tenaga Nuklir Nasional, 2017)
TEMPERATURE DEPENDENCE OF PRIMARY SPECIES G(VALUES) FORMED FROM RADIOLYSIS OF WATER BY INTERACTION OF TRITIUM β-PARTICLES. G(values) are important to understand the effect of radiolysis of Nuclear Power Plant (NPP) cooling water. Since direct measurements are difficult, hence modeling and computer simulation were carried out to predict radiation chemistry in and around reactor core. G(values) are required to calculate the radiation chemistry. Monte Carlo simulations were used to calculate the G(values) of primary species , H•, H2, •OH dan H2O2 formed from the radiolysis of tritium β low energy electron. These radiolytic products can degrade the reactor components and cause corrosion under the reactor operating conditions. G(values) prediction can indirectly contribute to maintain the material reliability. G(values) were calculated at 10-8, 10-7, 10-6 and 10-5 s after ionization at temperature ranges. The calculation were compared with the G(values) of g-ray 60Co. The work aimed to understand temperature effect on the water radiolysis mechanism by the tritium β electron. The results show that the trend similarity was found on the temperature dependence of G(values) of tritium β electron and g-ray 60Co. For tritium β electron, G(values) for free radical were lower than g-ray 60Co, but higher for molecular products as temperature raise at 10-8 and 10-7. The significant differences for these two type of radiations were on G(H2), G(•OH) and G(H•) at 10-6and 10-5 s above 200 oC.